20 YEARS OF THE LAW ON BRAZILIAN EDUCATION GUIDELINES AND BASES AND SPECIAL EDUCATION: CONSIDERATIONS AND REFLECTIONS - Carbone Carneiro, Relma Urel [UNESP]; Canazza Dall'Acqua, Maria Julia [UNESP]; Caramori, Patricia Moralis (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
The text tries to present some reflections on certain aspects regarding special education related to the 20-year period of validity of the Law on Brazilian Education Guidelines and Bases (LDBEN). It presents some considerations on the process that led to the formulation of a chapter about the argument. Three themes are presented as well. Two of them are considered as flexibility points and the third one highlights a more conservative aspect. The first mode discusses some points related to specific structural and instrumental conditions, planning, political-pedagogical project, teachers management and training and their multiple possibilities. Finally, it proposes some elements for reflection on the challenges that remain for the school to offer education for everyone.
Keywords: Special Education; Educational Politics; Legislation